Efektivitas Media Pembelajaran Berbasis Budaya Gici-Gici pada Pembelajaran Matematika di Sekolah Menengah Pertama - Matruty, Yosevita; Ratuanik, Mesak; Lerebulan, Elisabet; Halirat, Karten (Papanda, 2026)
This study aims to determine that by using learning media based on gici-gici culture in mathematics learning for class VIII of SMP Negeri 5 Tanimbar Selatan. The design and approach in this study used a qualitative approach. This type of research is a study that describes data in the form of words and describes phenomena or facts obtained in the study. The subjects in this study were students of class VIII of SMP Negeri 5 Tanimbar Selatan. Data collection techniques used were research documentation, written tests and interviews and observation. Data analysis techniques used were data collection, data reduction, data presentation and data verification or drawing conclusions. The results of the study show that by implementing the gici-gici culture learning media in the learning process, it can increase the effectiveness of learning through the test results of students who follow the learning process as evidenced by the results of student tests classified into three aspects, namely low because the learning process of these students is rarely active and rarely attends school so that it has an impact on the completion of essay test questions that are not correct, medium because the completion of essay questions is wrong and does not follow the stages of solving the questions correctly and high because students are able to work on essay test questions by paying attention to the stages of solving the questions correctly and being active in the learning process.